(untitled) - Thomsett, Michael C. (Hoboken, N.J., 2007)
An accessible introduction to A PROVEN TRADING STRATEGY GETTING STARTED IN SWING TRADING Swing trading is not a new idea. But, only recently-with the Internet opening up markets to virtually everyone-has this short-term technical trading strategy become a viable option for individual investors. There are many ways to profit from the swing trading method, and with Getting Started in Swing Trading, author Michael C. Thomsett will show you how to use this approach to quickly take advantage of short-term price movements found in today's dynamic markets. Written in a straightforward and accessible style, Getting Started in Swing Trading: Explores many of today's most popular charting signals and explains how to recognize them Provides suggestions for picking stocks appropriate for your swing trading strategy Illustrates how options can be used within your swing trading program to mitigate risk and improve performance Analyzes the effectiveness of short selling within a swing trading strategy Outlines some restrictions on swing trading, including brokerage rules and requirements, and regulations about high-activity trading And much more Filled with in-depth insights and practical advice, Getting Started in Swing Trading will enhance your understanding of this proven trading method as well as improve the overall profitability of your portfolio.
Keywords: Investment analysis,Stocks,Phân tích đầu tư,Cổ phần